The Impact of Big Data Management Capabilities on the Performance of Manufacturing Firms in Asian Economy During COVID-19: The Mediating Role of Organizational Agility and Moderating Role of Information Technology Capability - Zhang, Junling; Li, Hualong (Frontiers in Psychology, 2022)
The main purpose of the study is to examine the impact of the big data management capabilities on the performance of manufacturing firms in the Asian Economy During Covid-19. In addition to this the study is also planned to examine the mediating role of organizational agility in the relationship between the big data management capabilities and the performance of Chinese manufacturing firms during COVID-19.Lastly the study has examine the moderating role of information technology capability in the relationship between the big data management capabilities and performance of Chinese manufacturing firms during COVID-19. This study adopted the quantitative method of research with a cross-sectional technique. This study employed a questionnaire to gather the data as a research instrument. This study has used the purposive sampling method by keeping in mind the context of the study. Employees of the Chines SMEs that were at least 10 years old were the population of the current study. The research model was being analyzed by employing the “Partial Least Squares” technique through statistical software the Smart PLS 3. The results are in line with the proposed hypothesis. The present study contributed to the literature by suggesting characteristics that promote or prevent the organization to successfully implementing big data and pointed out that showing resistance in information management system implementation may have different effects on the organization. Besides, the study also discussed the relationship between such information systems and the organization. Findings of these two factors provide insights for the practitioners and researchers in assessing the success or failure of organizations for using big data.